1987
DOI: 10.3382/ps.0660683
|View full text |Cite
|
Sign up to set email alerts
|

Broiler Breeder Performance in Response to Diet Protein and Energy

Abstract: Two hundred and forty Hubbard X Hubbard broiler breeders at 19 weeks of age were weight-sorted and transferred to individual laying cages where one of six experimental diets was provided to 41 weeks of age. Each diet was represented by 10 replicate groups of 4 individually caged and fed birds. Feed allocation was gradually increased to 150 g/bird per day, which provided 19 or 25 g crude protein and either 325, 385, or 450 kcal metabolizable energy (ME)/bird per day. Hens were inseminated every 7 days with .05 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 8 publications
5
20
2
1
Order By: Relevance
“…This result is consistent with the findings of Robinson and Wilson (1996) who concluded that excessive body weight in broiler breeder female was negatively correlated with hen-day egg production. The present finding is also supported by Spralt and Leeson (1987).…”
supporting
confidence: 81%
“…This result is consistent with the findings of Robinson and Wilson (1996) who concluded that excessive body weight in broiler breeder female was negatively correlated with hen-day egg production. The present finding is also supported by Spralt and Leeson (1987).…”
supporting
confidence: 81%
“…Zebra finches (Taeniopygia guttata), whose diets were supplemented with protein, laid larger eggs with a greater proportion of yolk and albumen protein (Williams, 1996), and it has been suggested that dietary protein may be a direct and an indirect factor influencing the allocation of lipid and protein stores in laying birds (Carey, 1996). Egg weight and yolk content of broiler breeders also increased as dietary protein and energy increased (Spratt & Leeson, 1987). In contrast, increasing the dietary amino acid and protein resulted in an increase in egg weight, but a decrease in albumen quality in laying hens (Hammershøj & Kjaer, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, many researchers reported the positive effects of dietary protein on egg weight (Gunawardana et al, 2008; King'ori et al, 2010;Shim et al, 2013). Also, Spratt & Leeson (1987) reported that an increase in egg weight and consequently in chick weight increased when protein content in isoenergetic diet was changed from 12.70% to 16.70% for broiler breeder hens. The results of this studies indicated that egg and hatching chick weight increased with increasing crude protein in isoenergetic diet.…”
Section: Egg Weight and Hatching Chick Weightmentioning
confidence: 99%
“…Therefore, the relationship between egg weight and protein levels of hen diet should be taken into consideration for hatching chick weight. Spratt & Leeson (1987) reported that a reduction in egg weight and consequently in chick weight decrease when dietary protein content was reduced from 16.70% to 12.70% for broiler breeder hens.…”
Section: Introductionmentioning
confidence: 99%